Hubungan kepatuhan kunjungan antenatal care (ANC) dan pola makan dengan kejadian anemia pada ibu hamil - Puteri Ayu Nurhaliza; Siti Patonah; Wiwik Utami; Novia Dwi Astuti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Anemia in pregnant women is a health problem that affects the mother and fetus. Compliance with antenatal care (ANC) visits and good diet play a role in preventing anemia. However, culture and community beliefs influence the diet of pregnant women, Transcultural Nursing emphasizes the importance of considering cultural factors in health services so that education is more effective. Purpose: To analyze the relationship between compliance with ANC visits Health Center. Method: The design of this study was correlational analytic with a cross-sectional approach. The sample consisted of 40 pregnant women in the third trimester selected by purposive sampling. Data was collected through medical record observations, diet questionnaires, and hemoglobin level examinations, then analyzed using the Chi-Square test. Results: ANC visits in pregnant women showed that 87.5% were non-compliant and were not significantly related to anemia (p = 0.496). Diet was mostly good (65%) and sufficient (35%), but also not significant for anemia (p = 0.232). Thus, diet remains a risk factor (OR = 4.167). A cultural approach is needed in education because beliefs about food taboos affect the nutritional intake of pregnant women. Conclusion: ANC visits and diet are not significantly related to the incidence of anemia, but diet remains a risk factor (OR = 4.167). Suggestion: Health workers need to implement Transcultural Nursing in nutrition education, adapting to local culture so that pregnant women understand the importance of nutrition and compliance with ANC visit.